Comphensive guide to Mosby's physical examination - 4 0 16; Seidel, Henry M.; 5 (Singapore : Mosby/Elsevier, 2011)
Mosby's Guide to Physical Examination is a comprehensive textbook of physical examination, history-taking, and health assessment with a unique emphasis on differential diagnosis and variations across the lifespan. The book conveys a uniquely compassionate, patient-centered approach to physical examination with a strong evidence-based foundation. This book has Clinical Pearls boxes which give brief clinical insights with expert tips on techniques, findings, and patient teaching; Mnemonic boxes deliver engaging auditory, visual, and other memory cues to help you remember series of assessment or exam steps; Physical Variations boxes detail multicultural considerations for assessing patients from diverse ethnic and cultural groups; Staying Well boxes describe holistic approaches to health promotion and patient teaching; Risk Factors boxes highlight modifiable and nonmodifiable risk factors for a variety of conditions; Differential Diagnosis boxes give comparisons of expected findings for similar conditions and explain how disease presentations vary; Physical Examination boxes provide current data on the most effective techniques for delivering quality patient care; Functional Assessment boxes focus on the patient's functional abilities and present a holistic approach to patient care; Downloadable text and PDA summaries allow for quick review of the key steps in each system exam; Dynamic learning exercises on the companion website test your knowledge and provide instant feedback on your progress; Updates throughout reflect the latest research findings and evidence-based practice for techniques, normal and abnormal findings, genetics, and assessment; 60 video clips demonstrate exam techniques for each system and are downloadable for use on Video iPod devices; 25 new anatomy and physiology animations provide narrated explanations of processes beneath the skin; New audio chapter summaries, downloadable for use on MP3 players, offer a convenient way to review key content on the go; New 3-column tables featuring Pathophysiology, Subjective Data, and Objective Data provide an illustrated reference that allows for quick and accurate comparisons; and 75 new illustrations and dozens of new photos of normal and abnormal findings help to clarify anatomic concepts and exam techniques.--BOOK JACKET.
Other title: Guide to physical examination.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; methods.;methods. -- Physical diagnosis.;Physical Examination;Medical History Taking -- 20; 20; 2